Dental faculty and student views of didactic and clinical assessment: A qualitative description study. (30th June 2020) - Perez, Arnaldo; Green, Jacqueline L.; Starchuk, Colleen; Senior, Anthea; Compton, Sharon M.; Gaudet‐Amigo, Gisele; Lai, Hollis; Linke, Bernard; Patterson, Steven
Abstract: Objective: Although assessment is essential to accurately represent student learning, little is currently known about student and faculty perceptions of assessment in dental schools. Our study aimed to explore faculty and student views of didactic and clinical assessments in the School of Dentistry at the University of Alberta. Method: Qualitative description informed the study design. Data were collected through focus groups and analysed inductively using manifest content analysis. Results: Five focus groups were conducted with faculty (n = 34) and three with students (n = 19). Faculty and student views of assessment were related to improvements made (perceived positive changes), improvements needed (perceived limitations) and improvements recommended (recommendations to improve perceived limitations). Faculty and students reported that improvements made (eg adequacy of assessment to students' levels of training) varied across instructors, courses and learning environments. Both faculty and students perceived clinical assessments as less appropriate than didactic assessments. Faculty perceived limitations were mostly related to assessment appropriateness, especially assessment accuracy and comprehensiveness, whilst student perceived limitations included other issues related to appropriateness (eg misalignment with course objectives) as well as issues related to assessment volume, pace and scheduling. Similarly, faculty recommendations focused on enhancing the assessment of clinical competencies, whilst students' recommendations aimed to also improve assessment scheduling, volume and usage (eg for learning purposes). Conclusions: Faculty and student views of assessment complemented one another. Our data show that assessment in dental education is multidimensional, so that multilevel strategies may be needed to improve this component of dental curricula.